Hepatoprotective effect of ethanol extract of matoa leaves (Pometia pinnata) against paracetamol-induced liver disease in rats - Yosua Maranatha Sihotang; Eka Windiasfira; Hendro David Ginola Barus; Herlina Herlina; Rennie Puspa Novita (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2017)
The hepatoprotective effects of matoa leaves were evaluated by paracetamol-induced injury in rat’s hepatocytes. The ethanolic extract of matoa leaves (EEML) at doses of 200, 300, 500 mg/kg, po and silymarin at dose of 100 mg/kg, po were given for seven days. Silymarin was given as the reference drug. Hepatoprotective effect was studied by measuring the level of AST, ALT, ALP and total protein in serum. In vivo, oral treatment with EEML at dose of 500 mg/kg significantly reduced AST, ALT, ALP in serum whereas total protein was not significantly reduce in each groups. These results indicate that the hepatoprotective action of EEML is likely related to its potent antioxidative activity. Neutralizing reactive oxygen species enhancing the activity of original natural hepatic-antioxidant enzymes may be the main mechanisms of EEML against paracetamol-induced injury. Keywords: Matoa Leaves (Pometia pinnata), Paracetamol, Silymarin, Hepatoprotection